Prevalence and characteristics of potential drug-drug interactions in hospitalized atrial fibrillation patients receiving anticoagulant therapy - Putri, Atika; Ilma, Dewi Latifatul; Suryoputri, Masita Wulandari; Endriastuti, Nialiana Endah (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2024)
Background: Anticoagulants are essential for stroke prophylaxis in atrial fibrillation but carry significant interaction potential with commonly used medications. Understanding the prevalence and patterns of these interactions is crucial for optimizing therapy. Objective: To assess the incidence and characteristics of potential drug-drug interactions (DDIs) in hospitalized atrial fibrillation patients receiving anticoagulant therapy. Methods: This retrospective, descriptive observational study analyzed medical records of 324 atrial fibrillation patients hospitalized between January 2019 and December 2021 at a regional hospital in Banyumas Regency. Potential DDIs were assessed using Lexicomp, Drugs.com, and Merck Manual databases, and categorized by severity, mechanism, and clinical manifestation. Results: Nearly all patients (98.90%) experienced at least one potential DDI. Of 1,249 identified DDI events, most were moderate in severity (83.27%) and primarily involved warfarin (69.73%). Pharmacodynamic mechanisms predominated (51.24%), and decreased anticoagulant efficacy was the most common potential clinical manifestation (64.21%). Warfarin accounted for most pharmacokinetic (10.49%) and pharmacodynamic (32.42%) interactions. Elderly patients (>65 years) constituted the largest population group (40.74%), and most patients (65.74%) had atrial fibrillation as a secondary diagnosis. Conclusion: The high prevalence of potential DDIs involving anticoagulants in hospitalized atrial fibrillation patients underscores the need for vigilant medication management, particularly for patients receiving warfarin and those with multiple comorbidities.